Studi Kelayakan Sistem Instalasi Listrik pada Ruang Operasi Rumah Sakit Umum Daerah Kepahiang - Sandi Sandi Carnolis; Alex Surapati (MAJALAH TEKNIK SIMES, 2017)
The supply of electricity and continuous indispensable to guarantee the operating room surgery went well, secure, and seamless. This study aimed to evaluate the feasibility of existing electrical installation systems in hospitals, such as electrical distribution systems, electrical installation system, grounding system and shrinkage stress occurs and light intensity on the field work in the operating room. The results of the calculations obtained for qualification In MDP incoming cables of 25.47 A using NYFGBY 4x50 mm2 cable types. Value In a cable from the outgoing to the incoming MDP SDP OK obtained at 15.32 A. In the security system at 152.09 incoming MDP A. In the security SDP of 25.47 A. The intensity of illumination on the work plane measurable range 687-710 lux, grounding wire using a type BC 50 mm2 mounted on MDP and SDP OK. The value of the voltage drop of MDP to SDP accounted for 7,84Volt, and the percentage fall in voltage of 3.6%.